ANALISIS INSTRUMEN PENUGASAN MENULIS KREATIF DALAM BUKU SISWA BAHASA INDONESIA FASE F KURIKULUM MERDEKA - Putra , Natanael Ricky; Basuki, Imam Agus; Harsiati, Titik (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This article aims to analyze the quality of the creative writing assignment instrument for literature in the Indonesian Language Student Book of the Independent Curriculum Phase F (grades XI and XII), especially in terms of construct validity and cognitive level classification based on Brown's Creative Writing Taxonomy (C1–C3). The study used a qualitative approach with a document analysis method, with the main source Cerdas Cergas Berbahasa dan Bersastra Indonesia for grades XI and XII. The focus of the analysis was on four types of literary writing assignments: writing short stories from personal experiences, composing poetry based on short stories, writing drama scripts from short stories, and writing short stories with environmental themes. The results of the study showed that most assignments were at the C2 level (functional), with guided writing demands but still providing limited space for expression. Content and construct validity were relatively high because the assignments generally represented literary skills such as building plots, creating characters, and using language styles. However, the absence of an explicit assessment rubric and the lack of assignments at the expressive level (C3) indicated a gap between the curriculum aspirations and the available forms of assessment. Therefore, improving assignment design and developing measuring instruments that support ideational creativity is very necessary so that assessments are more authentic and in line with learning outcomes in the Independent Curriculum.